er-Ravzü’l-ünüf fî şerhi’s-sîreti’n-nebeviyye li İbn Hişâm - 880-01 Süheylî, Abdurrahman b. Abdullah, 1114-1185. (Kahire Kahire Kahire)
&lt 6 &gt cilt (1. c. 462 sayfa ; 2. c. 447 sayfa ; 3. c. 476 sayfa ; 5. c. 488 sayfa ; 6. c. 612 sayfa ; 7. c. 615 sayfa)